Principles and current clinical landscape of multispecific antibodies against cancer - Elshiaty, Mariam; Schindler, Hannah; Christopoulos, Petros (International journal of molecular sciences, 2021)
Building upon the resounding therapeutic success of monoclonal antibodies, and supported by accelerating progress in engineering methods, the field of multispecific therapeutic antibodies is growing rapidly. Over 140 different molecules are currently in clinical testing, with excellent results in recent phase 1-3 clinical trials for several of them. Multivalent bispecific IgG-modified formats predominate today, with a clear tendency for more target antigens and further increased valency in newer constructs. The strategies to augment anticancer efficacy are currently equally divided between disruption of multiple surface antigens, and additional redirection of cytotoxic T or NK lymphocytes against the tumor. Both effects complement other modern modalities, such as tyrosine kinase inhibitors and adoptive cell therapies, with which multispecifics are increasingly applied in combination or merged, for example, in the form of antibody producing CAR-T cells and oncolytics. While mainly focused on B-cell malignancies early on, the contemporary multispecific antibody sector accommodates twice as many trials against solid compared to hematologic cancers. An exciting emerging prospect is the targeting of intracellular neoantigens using T-cell receptor (TCR) fusion proteins or TCR-mimic antibody fragments. Considering the fact that introduction of PD-(L)1 inhibitors only a few years ago has already facilitated 5-year survival rates of 30-50% for per se highly lethal neoplasms, such as metastatic melanoma and non-small-cell lung carcinoma, the upcoming enforcement of current treatments with “next-generation” immunotherapeutics, offers a justified hope for the cure of some advanced cancers in the near future.
Gesehen am 26.07.2021